First-principles study on high-pressure phases and compression properties of gold-bearing intermetallic compounds. (16th November 2022) - Li, Bingtan; Liu, Hanyu; Liu, Guangtao; Chen, Kaiguo
Abstract: Compared to elemental gold (Au), Au-based alloys have attracted wide attention for their economy and superior performance stemming from their distinctive physicochemical properties. The study of the structural characterization for alloy materials remains one of the fundamental issues associated with their future applications essentially. In this work, we theoretically explore some typical intermetallic compounds of Au-based alloys under high pressure, which has been an effective means to generate intriguing crystal configurations with unexpected behaviors. Our ab initio simulations find that Fd -3 m -AuRb, Fd -3 m -AuBa, and Fd -3 m -AuLa become stable above ∼10 GPa, and Pmmn -AuAl becomes stable above ∼20 GPa. Further investigations of their compression behaviors reveal that the bulk moduli of Au-based alloys can be greatly reduced by combining alkali and alkaline earth metals. The present results have unraveled the high-pressure phases of Au-bearing compounds and provide insights for exploring their important compressibility that is strongly relevant to the containing non-Au elements.